Correlation of Anthropometric Indices with Fasting Blood Glucose and Blood Pressure among University Students in Kano, Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Studies have suggested superiority of measures of central obesity over body mass index (BMI) in predicting cardiovascular risk. This multiplicity of anthropometric indices has led to inconsistency in their correlation with fasting blood glucose (FBG) and blood pressure.Aim:The aim of this study was to determine the prevalence of obesity using different anthropometric indices and their correlation with FBG and blood pressure among university students in Kano, Nigeria.Materials and Methods:One hundred and forty-eight participants were randomly selected for the study. Anthropometric indices, FBG and blood pressure were measured following standard protocols. Data were analysed using IBM SPSS version 23.0. Pearson’s correlation coefficient was used to determine the relationship between quantitative variables.P≤ 0.05 was considered statistically significant.Results:The mean age of the participants was 22.09 years ± 4.03. The prevalence of obesity was: BMI – 4.8%, waist circumference (WC) – 23.1%, waist–hip ratio (WHR) – 31.76% and waist–height ratio (WHtR) – 31.76%. BMI was positively correlated with diastolic blood pressure (DBP) and mean arterial pressure (MAP). WC was positively correlated with systolic blood pressure (SBP), DBP and MAP. WHtR was positively correlated with SBP, DBP and MAP among female participants only. WHR was negatively correlated with DBP and MAP in male participants only. WC, WHtR and WHR were positively correlated with FBG among female participants only.Conclusion:The prevalence of obesity among undergraduate students in Kano is high. There was a wide variation in the correlation between anthropometric indices and FBG and blood pressure.